Study of Didactic Transposition: Exploration of Taught Knowledge in Revealing Learning Obstacles for Madrasah Students - Agung Wicaksono; Didi Suryadi; Siti Fatimah; Suhendra Suhendra; Indah Suciati; Arsyil Waritsman (Jurnal Pendidikan Islam, 2025)
Didactic transposition helps bridge the gap between formal mathematical knowledge and classroom instruction, ensuring more effective material delivery aligned with students’ needs. The purpose of this study was to explore how linear equations of one variable are taught to eighth-grade students at Madrasah Tsanawiyah based on the didactic transposition approach. This study focuses on the knowledge transfer stage of a didactic transposition study on linear equations of one variable, using qualitative research with a descriptive method. The study’s results showed that the presentation of material in the teaching and learning process led to a shift in understanding of linear equations of one variable from the concept of linear equations of one variable in a didactic context. Incomplete explanations of linear equations with one variable cause learning obstacles. Ontogenic obstacles arise from students’ cognitive limitations, epistemic obstacles from conceptual complexity, and didactic obstacles from ineffective teaching strategies. This study is conducted because didactic transposition can bridge the gap between formal mathematical knowledge and classroom instruction, yet it may also create learning obstacles. The findings can help improve teaching strategies by addressing conceptual gaps and learning obstacles, making mathematics instruction more effective for students at Madrasah Tsanawiyah.